Canadiana Bruxellensia: Two Canadian Manuscripts at the Royal Library of Belgium in Brussels - Verweij, Michiel (Archivaria, 2006)
This article presents two documents on Canada, preserved in the Department of Manuscripts of the Royal Library of Belgium (Koninklijke Bibliotheek van België/Bibliothèque royale de Belgique) in Brussels. One is a personal notebook by a Major Henry Scott who visited Canada in 1886–1889; the other is a photo album presented to the participants in a journey through Canada following a congress of the British Medical Association in 1930. RÉSUMÉ Cet article présente deux documents relatifs au Canada, conservés dans le Cabinet des Manuscrits de la Bibliothèque royale de Belgique (Koninklijke Bibliotheek van België), à Bruxelles. Le premier est le carnet personnel d’un Major Henry Scott, qui fit une visite au Canada en 1886–1887; l’autre est un album-photo présenté aux participants d’un voyage à travers le Canada, suite à un congrès de la British Medical Association en 1930.